An Hα–X-Ray Surface-Brightness Correlation for Filaments in Cooling-Flow Clusters - Olivares-Sepulveda, V (Nature Research, 2025)
Massive galaxies in cooling-flow clusters display clear evidence of feedback from active galactic nuclei (AGNs). Joint X-ray and radio observations have shown that AGN radio jets push aside the surrounding hot gas and form cavities in the hot intracluster medium (ICM). These systems host complex, kiloparsec-scale, multiphase filamentary structures, from warm and ionized (10,000 K) to cold and molecular (<100 K). These striking clumpy filaments are believed to be a natural outcome of thermally unstable cooling from the hot ICM, probably triggered by feedback processes while contributing to feeding the AGN via chaotic cold accretion (CCA). However, the detailed constraints on the formation mechanism of the filaments are still uncertain, and the connection between the different gas phases has to be fully unveiled. By leveraging a sample of seven X-ray-bright cooling-flow clusters, we have discovered a tight positive correlation between the X-ray surface brightness and the Hα surface brightness of the filaments over two orders of magnitude, as also found in stripped tails. We further show the quantitative consistency of such a relation with CCA predictions by leveraging hydrodynamical simulations. This discovery provides evidence for a shared excitation mechanism between hot and warm filaments, where multiphase condensation, triggered by AGN feedback, drives their tight co-evolution. © The Author(s), under exclusive licence to Springer Nature Limited 2025.